An Analysis of Deixis Used in Soundtrack Lyrics of Barbie Movie - Khaira, Rahmatul; Zaim, M. (English Language and Literature, 2024)
This research aims to find the types and functions of deixis in the lyrics of the Barbie movie soundtrack. Data were collected from the soundtrack's lyrics and analyzed using Huang’s (2007) theoretical framework. The study identified 377 data of deixis, highlighting its crucial role in character development and personal references. Social deixis, with 57 data, and spatial deixis, with 47 data, underscore the significance of social relationships and locational context within the narrative. Temporal deixis, appearing 33 times, delineates the temporal framework of the lyrics. Discourse deixis and emotional deixis, with 16 and 4 data respectively, are less frequent, indicating that while references to the ongoing discourse and expressions of emotional proximity are present, they are less central to the lyrical content. This analysis underscores the multifaceted nature of deixis in enriching the narrative and emotional depth of the lyrics.